Small bowel obstruction caused by a true ileo-ileal knot: a rare case successfully treated by prior ligation of mesenteric vessels - Kohei Kanamori; Kazuo Koyanagi; Hitoshi Hara; Kenji Nakamura; Kazuhito Nabeshima; Miho Yamamoto; Yamato Ninomiya; Tadashi Higuchi; Kentaro Yatabe; Mika Ogimi; Kohei Tajima; Masaki Mori; et al. (Surgical Case Reports, 2021)
Abstract Background Intestinal knot formation, in which two segments of the intestine become knotted together, can result in intestinal obstruction. An ileo-ileal knot refers to knot formation between two ileal segments and is a very rare benign disease. We report a case of strangulated bowel obstruction caused by true ileo-ileal knot formation. Case presentation An 89-year-old woman was referred to our hospital with the diagnosis of intestinal obstruction. Contrast-enhanced computed tomography revealed the small bowel forming a closed loop, with poor contrast effect. Based on the findings, the patient was diagnosed as having strangulated bowel obstruction, and emergency surgery was performed. At laparotomy, two segments of the ileum were found to be tied together forming a knot, and both segments were necrotic. Although it was necessary to release the strangulated small bowel, we did not immediately release the knot, but first proceeded with ligation of the mesenteric vessels to the strangulated small bowel to prevent dissemination of toxic substances from the necrotic bowel into the systemic circulation. The surgery was completed with resection of the necrotic ileum and anastomosis of the small intestine. The postoperative course was uneventful, and the patient was discharged home. Conclusion We encountered a case of strangulated bowel obstruction caused by true ileo-ileal knot formation. Resection of the necrotic small intestine without releasing the knot could be performed safely, and might be considered as an option of surgical procedure.